A study of cyclic and constacyclic codes over Z4 + uZ4 + vZ4. (2018) - Islam, Habibul; Prakash, Om
In this paper, we study some properties of cyclic and constacyclic codes over the ring R = Z4 + u Z4 + v Z4 where u 2 = uv = vu = 0. The generator polynomials and minimal spanning set for cyclic codes over R are determined. Further, (1 + 2 u ) - constacyclic codes are considered and find the cyclic, quasi-cyclic and permutation equivalent to a QC code over Z4 as the Gray images of (1 + 2 u ) - constacyclic codes over R .